Econometric study of the effect of unemployment and inflation on economic growth in Algeria for the period 1990-2018 using VECM model - CHERAKRAK, Samir; KEHAM, Wahiba; SID, Fatah (Journal of Human Sciences, 2020)
This study aims to measure and analyze the effect of the unemployment rate and inflation on the economic growth in Algeria for the period 1990-2018. This study was based on the error correction model and shock response functions. It has reached a causal relationship between growth rates, unemployment and inflation.It also found that a positive shock in the unemployment rate will have a negative impact on the growth rate in the short and medium term and a positive effect in the long term. A positive shock in the inflation rate will have a negative impact on economic growth in the long and short term; In addition, a positive shock in the rate of growth will have a significant negative impact on the unemployment rate and inflation in the long and short term.